Antibiotic resistance trends and species distribution of coagulase negative Staphylococci in a tertiary hospital setting - Alone, Rasika D.; Khetan, Seema; Shrikhande, Sunanda (International Journal of Research in Medical Sciences, 2025)
Background: Coagulase-negative Staphylococci (CoNS) have emerged as significant opportunistic pathogens, especially in nosocomial settings. Their increasing resistance to commonly used antibiotics has heightened the need for species-level identification and susceptibility profiling. Aim of this study was to speciate clinical isolates of CoNS, determine their antibiogram and study biofilm formation. Methods: In this cross-sectional study, 84 clinically significant CoNS isolates were identified by Standard biochemical tests and VITEK 2 system. Antibiotic susceptibility was determined by Kirby-Bauer disc diffusion method following CLSI (Clinical and laboratory standards institute) guidelines. Biofilm formation was assessed by tissue culture plate (TCP) method. Results: A total 84 clinically significant CoNS isolates were identified from blood, pus, urine, sterile body fluids and catheter tips. Out of 84 isolates, S. epidermidis (46.43%) was the most common species, followed by S. haemolyticus (22.61%) and S. saprophyticus (10.71%). Majority of CoNS were isolated from blood culture (57.15%) followed by pus (21.42%) and urine (14.29%). High resistance was observed against penicillin (92.9%), followed by gentamicin (63.1%), and cotrimoxazole (61.9%). The 54.8% isolates were MRCoNS (Methicillin resistant coagulase negative Staphylococci), with 21.42% showing inducible clindamycin resistance (ICR) among the 84 CoNS. All MRCoNS were sensitive to vancomycin and linezolid. Biofilm production was noted in 61.90% of isolates. Conclusions: Species-level identification and antibiotic resistance profiling of CoNS is crucial in clinical settings to avoid treatment failures. The high prevalence of MRCoNS and biofilm producers necessitates strict infection control and antibiotic stewardship.